2023
DOI: 10.3389/fnmol.2023.1128974
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Shank3 deficiency and paresthesia in autism spectrum disorder: A brief review

Abstract: Autism spectrum disorder (ASD) includes a group of multifactorial neurodevelopmental disorders characterized by impaired social communication, social interaction, and repetitive behaviors. Several studies have shown an association between cases of ASD and mutations in the genes of SH3 and multiple ankyrin repeat domain protein 3 (SHANK3). These genes encode many cell adhesion molecules, scaffold proteins, and proteins involved in synaptic transcription, protein synthesis, and degradation. They have a profound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 198 publications
0
2
0
Order By: Relevance
“…Rare inherited and de novo mutations in the SHANK3 gene have been reported for some time in animal and human studies, with associated impacts including alterations to synaptic maturation and function, disrupted neural communication, 'abnormal' brain development, and impaired cognitive and behavioural functioning (e.g. Boccuto et al, 2013;Huang et al, 2023;Uchino & Waga, 2013). As examples of how the SHANK3 mutation may influence ASD features, Guo et al (2019) found structural and functional alterations in the glutamatergic synapses of the pyramidal neurones in the anterior cingulate cortex in mice with a SHANK3 mutation and noted that this was linked to disrupted social behaviour.…”
Section: Synaptic Functioningmentioning
confidence: 99%
“…Rare inherited and de novo mutations in the SHANK3 gene have been reported for some time in animal and human studies, with associated impacts including alterations to synaptic maturation and function, disrupted neural communication, 'abnormal' brain development, and impaired cognitive and behavioural functioning (e.g. Boccuto et al, 2013;Huang et al, 2023;Uchino & Waga, 2013). As examples of how the SHANK3 mutation may influence ASD features, Guo et al (2019) found structural and functional alterations in the glutamatergic synapses of the pyramidal neurones in the anterior cingulate cortex in mice with a SHANK3 mutation and noted that this was linked to disrupted social behaviour.…”
Section: Synaptic Functioningmentioning
confidence: 99%
“…Over the past decade, research about the genetic correlates of ASD has witnessed remarkable advancements, progressing from monoclonal gene studies to contemporary large-scale investigations employing whole-genome sequencing (WGS) ( 8 ). Numerous highly reliable and reproducible risk genes have been identified, including Shank3 ( 9 ), Cntnap2 ( 10 ), and Nlgn3 ( 11 ), among others. These genes are associated with neuronal connectivity, synaptic function, and neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%